PENGARUH KONSELING INDIVIDU BERBASIS PENDEKATAN BEHAVIORISTIK TERHADAP KEDISIPLINAN PESERTA DIDIK KELAS VIII MTs. BUSTANUL HUDA KABUPATEN TEGAL - Syafiq, Mohamad (Program Studi Bimbingan dan Konseling Islam, 2022)
This research was aims to determine individual counseling based on a behavioristic approach, student discipline after the implementation of individual counseling based on a behavioristic approach, the effect of individual counseling based on a behavioristic approach on the discipline of 7th grade MTs students. Bustanul Huda Dawuhan, Talang District, Tegal Regency. This study uses a quantitative approach, this type of research is experimental research, the research design is a single group pretest-posttest experimental design. The results of the study show that the success of individual counseling based on a behavioristic approach is that students are very enthusiastic in participating in the process of individual counseling services based on a behavioristic approach, actively participating in individual counseling service activities based on a behavioristic approach, and counseling teachers are happy to make observations on students. as well as researchers. Student discipline before individual counseling services based on a behavioristic approach was in the low category, and after the individual counseling services based on a behavioristic approach were carried out it was in the high category.